Pengelolaan Wisata Tirta pada PT. Benoa Marine Recreation (BMR) Keluharan Tanjung Benoa, Kecamatan Kuta Selatan, Kabupaten Badung - Souhuwat, Elvina Marleen; Sukana, Made (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
The key of success in a company is on how the manager manages the company to survive, to compete, and dominate the market share. Therefore, management is a very important thing of a company, including a company which is running in the marine tourism sector. Benoa Marine Recreation is the first company which started water sport business in Bali and it is very interesting to determine its management. This research aims to determine the marine tourism management of PT Benoa Marine Recreation (BMR) in Tanjung Benoa village, Kuta Selatan subdistrict, Badung regency. The method used in this research is qualitative method and the data sources is primary data and secondary data. The data collecting method used in this research are observation, interview, and documentation and assisted with data analysis techniques. The result of this research explains that the management of Benoa Marine Recreation is very well by using kinship system. The functions of management are also running well, such as the planning has running properly, organizing also has running well. Every employes are involved, employees are doing their duty and obligation properly. The actuating has done by the general manager. The general manager also directs and motivates all employees. The coordination between boss and employees has interlaced very well. The controlling of water sport activities which is done by the operational manager also running well.   Keywords : Management, Marine Tourism, Water Sport